1994
DOI: 10.1056/nejm199411033311806
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Levonorgestrel Implants (Norplant) for Contraception in Adolescent Mothers

Abstract: The selection of Norplant by adolescent mothers as a method of contraception is associated with higher rates of continued use and lower rates of new pregnancy than the selection of oral contraceptives and does not affect the use of health care services, sexual activity, condom use, or the rate of sexually transmitted diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(43 citation statements)
references
References 19 publications
3
40
0
Order By: Relevance
“…23,24 Norplant insertion clearly has the potential to reduce the pace of subsequent adolescent childbearing. 31,32 However, the results of this and other studies suggest that if Norplant insertions and Depo-Provera injections are not accompanied by substantive changes in the daily living environment, (eg, those changes that are likely to make childbearing a less attractive life course option), early discontinuation and repeat pregnancies are likely to occur. 4,10 -16,23-25 Other investigators have also found that young mothers who report that they wanted their first baby are more likely to experience a closely spaced second birth.…”
Section: Discussionmentioning
confidence: 42%
“…23,24 Norplant insertion clearly has the potential to reduce the pace of subsequent adolescent childbearing. 31,32 However, the results of this and other studies suggest that if Norplant insertions and Depo-Provera injections are not accompanied by substantive changes in the daily living environment, (eg, those changes that are likely to make childbearing a less attractive life course option), early discontinuation and repeat pregnancies are likely to occur. 4,10 -16,23-25 Other investigators have also found that young mothers who report that they wanted their first baby are more likely to experience a closely spaced second birth.…”
Section: Discussionmentioning
confidence: 42%
“…Among adolescents attending a clinic in Baltimore in 1992-1993, 29% chose implants (36). High use prevalence has also been reported among postpartum teens: 50% chose injectables in one study (37) and 48% chose implants in another (38). Another study of postpartum adolescents reported that 43% of African-American, 33% of MexicanAmerican, and 24% of Caucasian women chose DMPA (39).…”
Section: Discussionmentioning
confidence: 92%
“…Of course, one can reverse the argument and postulate that the pill's additional pregnancy prevention effect is also very small if the male consistently uses the condom, so the adoption of the pill by the Japanese may be much less than in countries with less massive use of the condom. Even in the US, there is scant and mixed evidence on whether using hormonal contraception for pregnancy prevention reduces condom use for disease prevention [3][4][5][6]. Anecdotal evidence from Africa shows that women on subcutaneously placed hormonal implants may be less likely than women on injectables to have male partners who use condoms, because the implants are palpable and the male partners rationally reduce their use of the condom because their fear of impregnating the women is reduced (Rohler C, pers.…”
Section: Introductionmentioning
confidence: 96%